2010
DOI: 10.4049/jimmunol.0902016
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of the Recombinant Human C1 Inhibitor Serpin Domain: Insights into Heparin Binding

Abstract: Variants of the human C1 inhibitor serpin domain containing three N-linked carbohydrates at positions 216, 231, and 330 (C1inhΔ97), a single carbohydrate at position 330 (C1inhΔ97DM), or no carbohydrate were produced in a baculovirus/insect cells system. An N-terminally His-tagged C1inhΔ97 variant was also produced. Removal of the oligosaccharide at position 330 dramatically decreased expression, precluding further analysis. All other variants were characterized chemically and shown to inhibit C1s activity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…Moreover, the markedly lower activity of MMWH compared to UFH (M r 15 000) is plausible considering that UFH consists of chains with M r up to 35 000, whereas MMWH contains only 2.5% of chains with M r 12 000-15 000. In contrast to the activity of the heparin oligosaccharides VLMWH (18.2 ± 2.7% C1-INH potentiation at 6.25 μg/ml), which was in line with the results by Rossi et al [32], the inactivity of the PENTA oligosaccharides (-0.7 ± 2.8% C1-INH potentiation at 6.25 μg/ml) suggests the requirement of a minimum chain length or a minimum number of sulfate groups, respectively. The latter is concluded from the slight C1-INH potentiating effect (3.3 ± 5.3% at 6.25 μg/ml) of fondaparinux (FPX), the synthetic antithrombin-binding pentasaccharide with 8 (DS 1.60) instead of about 5 sulfate groups, which indicates additional relevance of the DS for the C1-INH potentiation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, the markedly lower activity of MMWH compared to UFH (M r 15 000) is plausible considering that UFH consists of chains with M r up to 35 000, whereas MMWH contains only 2.5% of chains with M r 12 000-15 000. In contrast to the activity of the heparin oligosaccharides VLMWH (18.2 ± 2.7% C1-INH potentiation at 6.25 μg/ml), which was in line with the results by Rossi et al [32], the inactivity of the PENTA oligosaccharides (-0.7 ± 2.8% C1-INH potentiation at 6.25 μg/ml) suggests the requirement of a minimum chain length or a minimum number of sulfate groups, respectively. The latter is concluded from the slight C1-INH potentiating effect (3.3 ± 5.3% at 6.25 μg/ml) of fondaparinux (FPX), the synthetic antithrombin-binding pentasaccharide with 8 (DS 1.60) instead of about 5 sulfate groups, which indicates additional relevance of the DS for the C1-INH potentiation.…”
Section: Discussionsupporting
confidence: 92%
“…bridging), Beinrohr et al [49] suggested a so-called sandwich-mechanism for the potentiation of C1-INH by polyanions with a heparin binding site in the contact area of the serpin-protease encounter complex. The experiments by Murray-Rust et al [50] confirmed that polyanion interactions with both C1-INH and C1s play a vital role in the mechanism of accelerating the reaction between C1s and C1-INH and both Rossi et al [32] and Rajabi et al [51] proved the binding of heparin to C1-INH as well as C1s by surface plasmon resonance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies provide a firm basis to guide a full elucidation of the molecular details underpinning the kinetic mechanism by which C1s interacts with C4. It is possible that the identified exosite also plays a role in the binding of highly sulfated heparin by C1s, an interaction that is vital for full regulation of the protease by the serpin, C1 inhibitor (37,38). Because unregulated complement activation underlies many inflammatory diseases, the data revealed in this study provide a basis for the design of therapeutic molecules for the targeted prevention of activation of complement via the classical pathway.…”
Section: Discussionmentioning
confidence: 97%
“…Mutants with altered glycosylation in the serpin domain have been studied (Rossi et al, 2010) and are active. C1inh with an N-terminal truncation has been crystallized (2OAY.pdb), and a potential heparin binding site was identified, not at the helix D location (which is obscured by the N-terminal domain) as for AT, but at the enzyme-inhibitor interface (Beinrohr et al, 2007).…”
Section: Heparin the Complement System And Innate Immunitymentioning
confidence: 99%